Influence of Digital Policy and Governance Sustainability on Student Online Shopping Behavior Through Instagram - Malek Nur Afiqah Aqilah Binti Abdul; Wiranatakusuma Dimas Bagus; Aprizal Anggi (SHS Web of Conferences)
The objective of this investigation is to examine bibliometric attributes associated with and the interplay between digital policy, governance sustainability, and student online shopping behavior through Instagram, utilizing data from the Scopus database spanning the period from 2014 to 2024. This paper presents recommendations for prospective avenues of study and advancement in this domain. Employing VOSviewer software, 30 articles underwent bibliometric scrutiny, facilitating the visualization of patterns such as keyword co-occurrence. The findings revealed a conspicuous constraint in the exploration of sustainable digital governance influencing student online shopping, which remains underexplored. The most researched topics are online shopping (70%), e-commerce (13,33%), students (10%), e-lifestyle (3,33%), and e-service (3,33%). Keywords: Bibliometric Analysis, Online Shopping, Scopus, VOSviewer, Digital Policy